Twenty-Four-Hour Movement Behaviors in Adults and Older Adults before Total Knee Arthroplasty: a Study Based on Compositional Data Analysis - Lošťák, Jiří; Gába, Aleš; Dygrýn, Jan; Baláž, Ľuboš; Štefelová, Nikola; Gallo, Jiří (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY This study aims to describe and analyze the age differences in the 24-hour movement behavior patterns among a sample of adults and older adults with end-stage knee osteoarthritis referred for total knee arthroplasty (TKA). MATERIAL AND METHODS A total of 86 patients referred for TKA were included in this study. Sleep duration, sedentary behavior (SB), light physical activity (LPA), and moderate-to-vigorous physical activity (MVPA) were assessed using multi-day 24-hour raw data from wrist-worn accelerometers. Compositional data analysis was used to analyze the differences between the age categories. RESULTS On average (SD), the adults were 59.0 (± 4.9) years; 63% female. The older adults were 72.4 (± 5.5) years; 58% female. The adults reached 23.9 milli-gravitational units (mg) as a mean acceleration over the whole day; 34% (8.1 h/day) of the time was classified as sleep, 48.9% (11.7 h/day) as SB, 12.1% (2.9 h/day) as LPA, and 5.1% (72.9 min/day) as MVPA. The older adults reached 21.3 mg; 35.2% (8.4 h/day) of the time was classified as sleep, 50.4% (12.1 h/day) as SB, 11.3% (2.7 h/day) as LPA, and 3.1% (44.9 min/day) as MVPA. Compared with the older adults, the proportion of time spent in total MVPA (P = 0.008) and MVPA bouts of ≥1 min were greater (P ≤ 0.028) in the adult group, while the proportion of time spent in total SB was lower (P = 0.045). No age difference was found for the proportion of time spent asleep. DISCUSSION Sleep, SB, and PA are exclusive and exhaustive parts of the overall 24-h day. Using accelerometer-based measures of 24-hour movement behavior to describe these behaviors more accurately is crucial for a better understanding of patients with end-stage KOA. CONCLUSIONS Our findings suggest that the adults and older adults referred for TKA are physically active despite suffering from severe knee osteoarthritis. Such a high level of physical activity may be difficult to increase by TKA postoperatively. If replicated by other studies, 24-hour movement behaviors should be implemented among the examinations required before TKA. Key words: knee osteoarthritis, accelerometer, sedentary behaviour, physical activity, sleep, 24-hour lifestyle behaviour.
Keywords: Female; Sedentary Behavior; Arthroplasty, Replacement, Knee; Humans; senioři; cvičení; Male; Aged; analýza dat; Exercise; ženské pohlaví; mužské pohlaví; sedavý životní styl; spánek; Data Analysis; lidé; Sleep; totální endoprotéza kolene